2017
DOI: 10.5296/ijele.v5i1.10696
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Saudi EFL University Students’ Attitudes towards the Use of Google Translate

Abstract: It is argued that the popularity of Google Translate is increasing and users are implementing this giant search engine for different purposes. Hence, this paper reports the results of a study on attitudes toward the use of Google Translate (GT). The participants were 92 Saudi EFL university English major students. A questionnaire was used as an instrument in this study. The results revealed that almost all of the subjects reported using GT. Vocabulary, writing and reading were the three most frequent purposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 4 publications
21
76
0
1
Order By: Relevance
“…This evidence indicates that GTA enables learners to participate in class and increase their interaction with their peers and the instructor by enhancing their pronunciation, reading and vocabulary. These results are consistent with the results presented by Alhaisoni and Alhaysony (2017), who reported that Google Translate was used by English language learners to assist them when understanding the meaning of unfamiliar vocabulary as a way to improve their reading skills. This evidence also shows that Google Translate increased learner's comprehension when translating keywords in class.…”
Section: The First Question: What Are the Affordances Of Gta As Percesupporting
confidence: 92%
See 4 more Smart Citations
“…This evidence indicates that GTA enables learners to participate in class and increase their interaction with their peers and the instructor by enhancing their pronunciation, reading and vocabulary. These results are consistent with the results presented by Alhaisoni and Alhaysony (2017), who reported that Google Translate was used by English language learners to assist them when understanding the meaning of unfamiliar vocabulary as a way to improve their reading skills. This evidence also shows that Google Translate increased learner's comprehension when translating keywords in class.…”
Section: The First Question: What Are the Affordances Of Gta As Percesupporting
confidence: 92%
“…Views pertaining to using Google Translate, as expressed by students majoring in English in Saudi Arabia, were reported by Alhaisoni and Alhaysony (2017). They explored the attitudes of ninety-two EFL students majoring in English.…”
Section: Google Translate and Language Learnersmentioning
confidence: 99%
See 3 more Smart Citations